Analysis of the Causes of Problems in Teaching Arabic to Class XI Students at Muhammadiyah Kartasura Vocational School - Priwitasari, Ashlih; Nashirudin, Muh (JUPE : Jurnal Pendidikan Mandala, 2024)
The negative impact on students when online learning was carried out during the previous pandemic carried over to face-to-face learning taking place in arabic language subjects. This is the cause of problems in teaching arabic, especially for eleventh grade’s students at SMK Muhammadiyah Kartasura. This research discusses the causes of problems in teaching arabic in school, especially at SMK Muhammadiyah Kartasura. The subjects of this research were arabic language teachers and eleventh grade’s students. This research uses a qualitative descriptive for research method with three data collection methods, namely observation method, interview method and documentation method. The results of this research found that there are causes of problems in teaching arabic, including student’s varying initial abilities, inadequate learning facilities, learning time of only one hour of a week, lack of student interest and motivation during the teaching and learning process in the classroom.